Flood and groundwater management for the mountain plateau of Omalos based on geoinformatics techniques - Kourgialas, N.N.; Karatzas, G.P. (Bulletin of the Geological Society of Greece, 2013)
A viable approach for flood and groundwater management in a mountain Plateau based on geoinformatics techniques is presented in this work. The proposed water management plan has two components: (a) the determination of the flood-hazard areas, and (b) the estimation of groundwater flow. For the first component, six factors were considered in order to estimate the spatial distribution of the flood hazardous areas: elevation, slope, land use, rainfall intensity, geology, and flow accumulation, The study area was divided into five regions characterized by different degrees of flood hazard ranging from very low to very high. The produced map of flood-hazard areas identifies the areas at high risk of flooding. The second component includes a groundwater management approach for estimating groundwater flow and the potential contamination risk. The proposed methodology can be used to objectively compare different scenarios based on anthropogenic interventions that can affect the flood-prone areas or the groundwater flow dynamic. All these approaches were applied at the Omalos Plateau in the White Mountains of Crete in Greece.